Treatment of wide-necked aneurysms with the Low-profile Visualized Intraluminal Support (LVIS Jr) device: a multicenter experience. (27th October 2016) - Grossberg, J A; Hanel, R A; Dabus, G; Keigher, K; Haussen, D C; Sauvageau, E; Linfante, I; Gonsales, D; Aguilar Salinas, P; Bouslama, M; Mayich, M; Nogueira, R G; et al.
Abstract : Background: The Low-profile Visualized Intraluminal Support (LVIS) Junior stent is newly approved for the treatment of wide-necked intracranial aneurysms. Objective: To report our multicenter experience with use of the LVIS Jr device. Methods: The neurointerventional databases of the participating institutions were retrospectively reviewed for aneurysms treated with LVIS Jr from the time of Food and Drug Administration approval until February 2016. All patients in the study period were included. Clinical presentation, aneurysm location, aneurysm size, vessel size, procedural complications, clinical and imaging follow-up were included in the analysis. Results: Eighty-five patients (54 female and 31 male) met the inclusion criteria for the study. Sixty-eight (80%) of the aneurysms were unruptured and the remainder were ruptured. The most common location of the treated aneurysms was anterior communicating artery (36%), middle cerebral artery bifurcation (22%), and basilar terminus (15%). The mean aneurysm size was 6.1 mm. The mean minimum parent vessel size was 2.3 mm. The LVIS Jr was successfully deployed in all but one case (99%). Initial angiographic results demonstrated Roy–Raymond class 1–2 occlusions in 61/84 patients (73%). At 6 months, 85% of the patients seen at follow-up had Roy–Raymond class 1–2 aneurysm occlusion. No procedure-related deaths occurred. Two cases of procedure-related complications (intraprocedural rupture and delayed rupture at day 2) were seen, leading to permanent neurologic morbidity. Both these cases were in patients with ruptured aneurysms. Conclusions: The LVIS Jr is a technically feasible, safe, and effective treatment for wide-necked intracranial aneurysms. Early results are promising but will need to be corroborated with longer-term follow-up.